A clinical study of the effectiveness of continuous epidural labour analgesia for vaginal delivery with 0.0625% bupivacaine with 0.0002% fentanyl - Kanna, Vijay; Hakkim, Abdul; Kanakasabai, Murugadoss; Govindan, Satheesh (International Journal of Research in Medical Sciences, 2017)
Background: Pain in labour is an extremely agonising experience for most women. Unrelieved labour pain produces many physiological changes which are detrimental to both the mother and the foetus. Various methods have been used to alleviate this pain. It is now well recognized that the only consistently effective method of pain in labour is lumbar epidural analgesia. Using a higher concentration of local anaesthetic agent to produce analgesia can be associated with undesirable side effects such as motor block, haemodynamic disturbances or interference with the progress of labour. Hence, various adjutants like adrenaline, clonidine and particularly opioids have been used to reduce the amount of local anaesthetics used and yet provide satisfactory analgesia. In view of the above, the present study assesses the clinical effectiveness of continuous lumbar epidural analgesia for vaginal delivery by using 0.0625% bupivacaine with 2µg/ml of fentanyl. Methods: Forty parturient admitted to Chennai Medical College and Hospital, Trichy, for vaginal delivery and who were in active labor was given 8 ml of 0.0625% bupivacaine with 2µg/ml of fentanyl. The parturient were assessed with respect to onset and duration of analgesia, maximum level of analgesia, pain scores, homodynamic parameters, motor block, side effects, mode of delivery and neonatal outcome. Results: The onset of analgesia was significantly faster in 0.0625% bupivacaine with 0.0002% fentanyl (9.7 minutes). A greater proportion of parturient achieved a maximum level of analgesia unto T8. The duration of analgesia was also significantly longer. The effectiveness of analgesia was better. There were no significant cardiovascular changes or any motor blockade. The side effects were mild sedation and in the parturient who received fentanyl. The mode of delivery and the Apgar scores of the neonates at 1 and 5 minutes were comparable. Conclusions: It was concluded that continuous lumbar epidural analgesia with 8 ml of 0.0625% bupivacaine with 2 µg of fentanyl improved the quality and duration of analgesia without producing any adverse effects on the mother or on the neonate.